Relationship between sleep quality and physical activity level in patients with ankylosing spondylitis. - Urkmez, B; Keskin, YAŞAR; KESKİN, YAŞAR (My University, 2019)
Introduction: Aim of this study was to investigate whether there is a relationship between exercise level and sleep quality in AS patients. Method: In our study, 150 AS patients and 80 healthy controls were included. Physical activity levels of both groups were evaluated using International Physical Activity Questionnaire (IPAQ-s) short form. Sleep quality of the participants was evaluated using Pittsburgh Sleep Quality Index (PSQI). Disease activity and functional status were measured by Bath AS Disease Activity Index and Bath AS Functional Index. Results: Subjective sleep quality, habitual sleep efficiency, sleep disturbance and Total PSQI scores were significantly higher in the patient group compared to healthy participants. The IPAQ score was found to be significantly lower in the patient group. Sleep disturbance, one of the components of PSQI, was found to be significantly higher in patients with low IPAQ score. Conclusions: Sleep disorders were found to be higher in AS patients than normal population and physical activity levels of AS patients were lower than normal population. In addition, Sleep disturbance was found to be high in patients with low physical activity. Therefore, it should be remembered that one of the causes of sleep disorders in AS patients may be related to low physical activity.